Использование приемов технологии критического мышления на уроках - Нугуманова, К.А. (My University, 2013)
Article focuses on teaching critical thinking in chemistry classes. The article describes the principles and techniques of critical thinking. Teacher shares experiences with technology critical thinking. Also describes the relationship of seven modules applied in the training.